Factors Causing Shark Loan of Households in Luang Prabang Capital, Luang Prabang Province - HER, Pheng (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study investigates the opinions of households in Luang Prabang on the formal and informal household institutions and the factors affecting shark loans. A questionnaire was used to collect data from 116 households from May 3 to August 30, 2024. 1). The analysis used the Likert scale and OLS robust model. The results showed high levels of satisfaction with the informal institutions (The average of shark loan amount per household is 21,077,586.21 kip, the expenditure is 4,250,000 kip per person while the income is 3,202,586.207 kip per person), it was found that the aspect of services is ( =3.991, =0.421), the price ( =3.959, =0.4218) and the promotion ( =3.800, =0.318) respectively. 2). The analysis of factors affecting shark loans in Luang Prabang using OLS robust shows that household expenditure has the largest influence, with a positive statistical significance level of 0.05. A decrease in household expenditure leads to a decrease in shark loans by 1.23. Informal credit service services also have a positive significance level of 0.05, increasing shark loans by 0.52%. Price has negative influences shark loans, with an increase in informal lending price decreasing shark loans by 0.48% with a significance level of 0.05.